INFLUENCE OF APPLICATION OF SANDWICH PANEL ON STATIC AND DYNAMIC BEHAVIOUR OF FERRY RO-RO RAMP DOOR - Tuswan, Tuswan; Zubaydi, Achmad; Piscesa, Bambang; Ismail, Abdi; Ariesta, Rizky Chandra; Ilham, Muhammad Fathi; Mualim, Fikri Indra (Journal of Applied Engineering Science, 2020)
The implementation of a sandwich panel on the marine structure needs better knowledge of mechanical behaviour, primarily static and dynamic response. The static and dynamic response is investigated due to the application of a sandwich panel on the ferry ro-ro ramp door using finite element software ABAQUS. Five modification models using different sandwich thickness and stiffener configuration were compared using static analysis to analyze a comparison of structural strength and weight saving. Additionally, the dynamic response was also investigated due to debonding problem. The influence of debonding ratio, geometry, number of debonding, debonding depth, debonding location, and boundary condition was carried out. Debonding was estimated by using free vibration analysis where the Lanczos method for eigen values extraction was applied. Result of the static analysis showed that Model C caused an increase in strength to weight ratio compared to the existing model. Furthermore, the natural frequency was being calculated as modal parameters to investigate the debonding problem. The natural frequency of the debonded model decreased due to discontinuity in the damaged area. The dynamic response using natural frequency change can be performed as a structural health monitoring technique.